Nandrolone improve synaptic plasticity at the hippocampus CA1 area and spatial localization in the Morris water maze of male adolescent rats. (September 2020) - Salimi, Zahra; Khajehpour, Lotfollah; Moradpour, Farshad; Moazedi, Ahmad Ali; Pourmotabbed, Ali; Zarei, Fatemeh
Highlights: Nandrolone improved spatial learning and memory in adolescent male rats. Castration abolished the effect of nandrolone on spatial learning and memory. Nandrolone enhanced the fEPSP-LTP in CA1 region of hippocampus. Castration reversed the effect of ND on the fEPSP-LTP. Abstract: Nandrolone is the most popular compound that are mainly abused. Experimental studies have reported that administration of nandrolone affects cognitive performance. So, the aim of this study is to evaluate the effect of nandrolone on spatial localization and synaptic plasticity of male adolescent rats. Experimantal groups received DMSO and nandrolone (10, 30 and 60 μg, i.c.v.). Another aim is to evaluate the role of castration on spatial learning and memory changes induced by nandrolone. Therefore, the rats of fifth and sixth groups were castrated and received DMSO or nandrolone. Analysis showed that escape latency and traveled distance in the group which received nandrolone (60 μg) were significantly lower than control group. Also, the escape latency and traveled distance in the group of castration which received nandrolone was significantly higher than nandrolone treated group. The results of field potential recording showed that fEPSP-LTP in nandrolone-treated group was higher than DMSO-treated group. The magnitude of fEPSP-LTP in the group of castration which received nandrolone was significantly lower than nandrolone-treated group. The results demonstrated that nandrolone improved spatial learning, but castration could abolished nandrolone-induced spatial learning improvement. These results indicating that at least some effect of nandrolone on learning induced through changes in gonadal function.